Comprehensive and combined omics analysis reveals factors of ischemia-reperfusion injury in liver transplantation. (31st January 2019) - Huang, Shanzhou; Ju, Weiqiang; Zhu, Zebin; Han, Ming; Sun, Chengjun; Tang, Yunhua; Hou, Yuchen; Zhang, Zhiheng; Yang, Jie; Zhang, Yixi; Wang, Linhe; Lin, Fanxiong; et al.
Aim: To explore molecular mechanisms underlying liver ischemia-reperfusion injury (IRI).Materials & methods: Four Gene Expression Omnibus datasets comprising liver transplantation data were collected for a comprehensive analysis. A proteomic analysis was performed and used for correlations analysis with transcriptomic.Results & conclusion: Ten differentially expressed genes were co-upregulated in four Gene Expression Omnibus datasets, including ATF3, CCL4, DNAJB1, DUSP5, JUND, KLF6, NFKBIA, PLAUR, PPP1R15A and TNFAIP3 . The combined analysis demonstrated ten coregulated genes/proteins, including HBB, HBG2, CA1, SLC4A1, PLIN2, JUNB, HBA1, MMP9, SLC2A1 and PADI4 . The coregulated differentially expressed genes and coregulated genes/proteins formed a tight interaction network and could serve as the core factors underlying IRI. Comprehensive and combined omics analyses revealed key factors underlying liver IRI, and thus having potential clinical significance.